Recipes as Memory Work: Slave Food - Halloran, Vivian Nun (Culture, theory and critique, 2012)
Contemporary African American and Afro-Caribbean cookbook authors and food memoirists seek to make the past of slavery seem more relevant and meaningful to twenty-first century readers by invoking the idea of 'slave food' as some common ground between themselves as eating subjects and the countless bondspeople who struggled to ensure their loved ones had enough nourishment to face the arduous tasks that lay before them every grinding day during the time of slavery. This essay turns to Marianne Hirsch's concept of 'postmemory' to elucidate the historical impulse to cook and eat the past as a way of understanding what it took to survive the trauma of chattel slavery practiced in the American South and throughout the Caribbean, by reading the individual recipes for slave food as textual snapshots that lend an aura of historical authenticity to each writer's representation of a communal legacy indelibly marked by the trauma of transatlantic slavery. Following Grant Farred's and Paul Gilroy's lead, I argue that the cookbook authors emerge as 'grounded vernacular intellectuals', whose professional knowledge of food preparation and the culinary arts give them the authority to discuss the cultural implications of cooking and eating traditional foodways, whereas the memoirists emerge as 'conventionally trained intellectuals' because of their formal education and institutional ties to the academy, as manifested in the pages of their books. Both sets of writers perform the memory work of honoring their unnamed slave ancestors through the publication of their food writing. Through the expository prose of the recipes, these texts invite the reader to join in the process of theorising the past of slavery by simulation (eating like slaves) and incorporation (eating like slaves). The goals of the type of memory work performed by these texts are to educate as well as feed its readers.